Recombinant expression and immunogenicity verification of Dabie bandavirus proteins Gn and Gc - Lou, Xiuyu; Mao, Haiyan; Lou, Yihan; Sun, Yi; Wang, Feng; Wang, Minjie; Zhang, Lijun; Fang, Zhihan; Yan, Hao; Zhang, Huijun (Frontiers in Microbiology, 2025)
IntroductionDabie bandavirus (DBV), a newly identified pathogen transmitted to humans via ticks bites, is the etiologic agent of severe fever with thrombocytopenia syndrome (SFTS). This disease is associated with a high mortality rate and constitutes a substantial threat to global public health. This study aimed to recombinantly express and characterize the immunogenicity and antigenicity of the DBV envelope proteins Gn and Gc.MethodsThe recombinant plasmids pET15b-Gn and pET15b-Gc were constructed and expressed in E.coil. The expressed proteins were purified, and rabbit polyclonal antibodies (anti-rGn-IgG and anti-rGc-IgG) were prepared through a four-immunization regimen. The antigenic specificity of the recombinant proteins was assessed, and their performance was evaluated for detecting DBV IgM antibodies in samples.ResultsThe rGn and rGc proteins were successfully expressed and purified, exhibiting molecular weights consistent with theoretical predictions. Antibody titers in immunized rabbits reached 1:512,000 for anti-rGn-IgG and 1:256,000 for anti-rGc-IgG. The proteins showed no significant cross-reactivity with other prevalent arboviruses. When used as antigens in assays, the rGn- and rGc-coated plates detected DBV IgM antibodies in 84.21% and 89.47% of positive samples, respectively.DiscussionThis study confirmed that the prokaryotically expressed DBV Gn and Gc proteins possess favorable immunogenicity, addressing the critical knowledge gap in evaluating of the immunogenic efficacy of prokaryotically expressed Gn and Gc. Currently, research on DBV’s pathogenic mechanisms, protein structure, and functions remains limited, and this findings provide a foundation for the development of DBV-related vaccines and drugs.